Does Canopy Height Determine the Pollen Viability and Stigma Receptivity? A Cross-population Observation on Shorea robusta Gaertn. f. - Bhattacharya, A. (Our Nature, 2012)
Pollen viability and stigma receptivity are prerequisite for successful pollination and fruit and/or seed set in flowering plants. The present paper deals with dependence of tree canopy height on pollen viability and stigma receptivity of Shorea robusta in a cultivated mature Dipterocarp forest. Pollen and stigma samples were collected from different canopy height and brought to the laboratory for direct assay. Pollen viability were studied following different stain tests using malachite green, acid fuchsin and TTC respectively and also using in vitro pollen germination in a nutrient medium consisting of sucrose and different salts of boron, calcium, magnesium and potassium. Stigma receptivity was studied by softening the tissues using sodium hydroxide and stained with water soluble aniline blue. The frequency of pollen viability increased steadily from low to high canopy height. The percentage of viable pollen was different for three different assays showing similar trend of increase. The middle and high canopy height did not show much variation in pollen viability compared to low canopies. The percentage of stigma receptivity increased steadily from low to high canopy height showing minor differences between them compared to pollen viability. So the tree canopy height may attain a vital role in determining pollen viability and stigma receptivity, the major factors for new offspring production in natural/cultivated forest settings. DOI: http://dx.doi.org/10.3126/on.v9i1.5732